Carbon dioxide sequestration of fly ash alkaline-based mortars containing recycled aggregates and reinforced by hemp fibres - Mastali, Mohammad (2018)
Carbon dioxide sequestration is crucial so targets for limiting global warming can be achieved. This paper discloses results of an investigation concerning the performance of fly ash/waste glass alkaline-based mortars with recycled aggregates reinforced by hemp fibres exposed to accelerated carbon dioxide curing. Compressive strength, carbon footprint and cost were studied on it. The results show that hemp fibres lead to a reduction on mechanical properties but not as high as reported by others. A high correlation was found between compressive and flexural strength The results also show that accelerated curing provides a high carbon sequestration. Furthermore, the use of at least 8% hemp fibres leads to carbon negative emissions -19,7 kgCO2eq/m3 for fly ash/waste glass alkaline-based mortars with recycled aggregates based composites.